Hydrazine and Urea Fueled-Solution Combustion Method for Bi2O3 Synthesis: Characterization of Physicochemical Properties and Photocatalytic Activity - Yayuk Astuti; Prisca Putri Elesta; Didik Setyo Widodo; Hendri Widiyandari; Ratna Balgis (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Bismuth oxide synthesis using solution combustion method fuelled by hydrazine and urea has been conducted. This study aims to examine the effect of the applied fuels, urea and hydrazine, on product characteristics and photocatalytic activity in degrading rhodamine B dye. Bismuth oxide synthesis was initiated by dissolving bismuth nitrate pentahydrate (Bi(NO3)3.5H2O) in a nitric acid solvent. Fuel was added and then stirred. The solution formed was heated at 300 ºC for 8 hours. The product obtained was then calcined at 700 ºC for 4 hours. Bismuth oxide synthesized with urea (BO1) and hydrazine (BO2) as fuels both obtained form of yellow powder. The formation of bismuth oxide is indicated by the vibrations of the Bi–O–Bi and Bi–O groups and the crystal structure of a-Bi2O3 in both products. Photocatalytic activity test showed that BO1 has a photocatalyst activity in degrading rhodamine B higher than that of BO2 with constant values of 3.83×10-5 s-1 and 3.43×10-5 s-1, respectively. The high photocatalytic activity can be examined through several factors, such as: band gap values, crystal structure, morphology, and surface area, acquired as a result of the use of different fuels in the synthesis process. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).